Efektivitas Terapi Murottal Al-Qur’an Terhadap Tingkat Kecemasan Ibu Hamil Trimester III di Wilayah Binaan Puskesmas Karangdoro Semarang - Yuni Astuti; Fitri Wahyuni; Shella Nur Jayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Third trimester pregnancy begins at 28-42 weeks of gestation. Pregnant women tend to look worried and will experience anxiety. One of the treatments to help reduce anxiety in third trimester pregnant women is Al-Qur'an murottal therapy. The purpose of this study was to analyze the effect of Qur'anic murottal therapy on anxiety levels in third trimester pregnant women. The research method is experimental with pre-post test design. This study was conducted by assessing the anxiety level of third trimester pregnant women before and after the Qur'an mu'rotal therapy. The sample size in this study was 17 respondents determined by purposive sampling. The results of this study indicate that there is an effect of giving Al Qur'an murottal therapy in reducing anxiety in third trimester pregnant women with a p value of 0.000. The conclusion of this study shows that the provision of murottal therapy Al Qur'an can reduce the anxiety level of third trimester pregnant women.